Effect of Cassia auriculata (Caesalpiniaceae) flowers on gentamicin-induced nephrotoxicity in rats / Manizheh Khalilpour Farshbafi - Farshbafi, Manizheh Khalilpour (2015)
While gentamicin is effective against severe gram-negative infections, its nephrotoxicity restricts clinical applications. This study was aimed at investigating effect of Cassia auriculata aqueous and polyphenolic extracts against gentamicininduced nephrotoxicity. Polyphenolic extract was prepared by extracting flower aqueous extract with ethyl acetate (1:1 v/v). Effect of C. auriculata aqueous or polyphenolic extracts on cellular viability and H2C>2 -induced cell death on Vero cells were measured by (MTS) assay. To examine nephroprotective effect, male Sprague- Dawley rats were pretreated with different doses of C. auriculata aqueous (100, 300,500 mg/kg/day, p.o.) or polyphenolic extracts (50, 100, 300 mg/kg/day, p.o.) for 2 weeks, followed by 8 days treatment with gentamicin (100 mg/kg, i.p.). To examine therapeutic effect, rats were injected with gentamicin (100 mg/kg, i.p.) for 8 days,followed by treatment with different doses of C. auriculata aqueous (100, 300, 500 mg/kg/day, p.o.) or polyphenolic extracts (50, 100, 300 mg/kg/day, p.o.) for 2 weeks. On day 22, rats were placed individually in metabolic cages and 24 h urine samples were collected. On day 23, rats were killed and blood was collected. Renal function was assessed by serum urea, creatinine, albumin, total protein, urine creatinine,urinary protein excretion and creatinine clearance ratio. Kidney was subjected to histopathologic examination. Expression levels of antioxidant genes (catalase,superoxide dismutase, glutathione peroxidase) and proinflammatory cytokines (IL-1 (3,TNF-a) were measured by RT-PCR. In vitro results indicated that pretreatment of Vero cells with both aqueous and polyphenolic extracts for 24 h significantly ameliorated the cytotoxicity of H2O2 in a concentration-dependent manner. Aqueous extract produced a maximal protection afforded by 50 pg/mL at which, cell viability was 67%. Polyphenolic extract showed higher protective effect as compared to aqueous extract with the maximum protection at 50-200 pg/mL with about 73% cell viability. In vivo results indicated that C. auriculata aqueous (300 mg/kg) and polyphenolic (100 mg/kg) extracts significantly reduced gentamicine-induced elevations in serum creatinine, serum urea and urine total protein. Gentamicin-induced decrease in serum total protein, serum albumin, urine creatinine, and creatinine clearance were restored. Histopathological evaluation of renal cortex of rats treated with C. auriculata aqueous or polyphenolic extracts showed protective and therapeutic effect against tubular necrosis, infiltration of inflammatory cells and thickening of basement membrane. Antioxidant genes were significantly up-regulated by C.auriculata aqueous or polyphenolic extracts. Gentamicin-induced excessive expression of proinflammmatory cytokines were normalized by C. auriculata aqueous and polyphenolic extracts. The findings suggest that C. auriculata aqueous (300 mg/kg) and polyphenolic (100 mg/kg) extracts possess nephronprotective and nephrocurative activities by enhancing renal antioxidant enzymes and inhibiting proinflammmatory cytokines.